Intimate partner violence: enduring abuse and twenty-first-century issues, challenges, and opportunities - Elizabeth, Laura (Rowman and Littlefield, 2025)
"While no act of scholarship can undo the abuse other survivors have endured, there is tremendous healing in confronting the reasons why domestic violence is still such a pressing social issue. This book helps readers to objectively assess how far we have come, and how far we have yet to go"--